An Electrochemical Sensing Platform for the Detection of Lead Ions Based on Dicarboxyl‐Calix[4]arene. Issue 3 (18th January 2018) - Nur Abdul Aziz, Siti Fatimah; Zawawi, Ruzniza; Alang Ahmad, Shahrul Ainliah
Abstract: A simple and highly sensitive electrochemical sensor COOH−C4 derived from dicarboxyl‐calix[4]arene modified on a screen printed gold electrode (Au) was developed for the determination of lead ions in water samples. A 3‐mercaptopropionic acid (MPA) monolayer was used as a template on the gold electrode for the surface modification with dicarboxyl‐calixarene. The modified electrodes were surface‐characterized using Fourier Transform infrared spectroscopy (FTIR). The data obtained proved the confirmation of each stage of the electrode modification. The electrochemical analyses of the COOH−C4 electrode showed an enhanced electrocatalytic activity and higher current towards Pb 2+ ions as compared to the bare Au and MPA/Au electrodes. Under optimum conditions, the differential pulse voltammetry response of COOH−C4 displayed a wide linear response ranging from 280–2500 μg/L for Pb 2+ with a detection limit of 6.2 μg/L. In addition, the fabricated electrode showed a high selectivity and stability towards the Pb 2+ ions in presence of possible interfering species. The present method was successfully applied to determine Pb 2+ ions in real samples with satisfactory precision, with a relative standard deviation of 3.12 % and an acceptable recovery of 92 %, which demonstrated the potential application of dicarboxyl‐calix[4]arene modified on electrodes for heavy‐metal sensing. Abstract :